Estimation of Leptin and Leptin Receptor Concentrations in Seminal Plasma of Primary Infertile Men - Ruqaya M. AL-Barzinji; Ahmed A. AL-Naqshbandi (مجلة كلية الطب, 2017)
Background: There are many sources for Leptin secretion, and it is activated by binding with its receptor known as leptin receptor, that play a role in male infertility. Objective: To assess the levels of leptin and leptin receptors in seminal plasma among primary infertile men and its impact on semen parameters. Patients and Methods: A case control study of 75 primary infertile males and 40 healthy individuals who were enrolled in this study during March 2013 to May 2013. Estimation of age, body mass index (BMI), semen analysis, seminal plasma leptin, leptin receptor and testosterone hormone concentration were done for all study subjects. Results: Highly significant difference found in mean of semen parameters of infertile male compared with healthy controls. Mean concentration of seminal plasma leptin and leptin receptor of infertile men were significantly were elevated, while serum testosterone concentration significantly decreased compared with healthy control. Conclusion: There is emerging evidence that the leptin concentration negatively impacts fertility through its correlation with age, BMI, testosterone hormone and semen parameters.